Emotional Intelligence: A Servant's Response in Forming a Paradigm Toward God Based on the Book of Habakkuk - Josua, Rezky Alfero; Sualang, Farel Yosua (Institut Agama Kristen Negeri Toraja, 2024)
Abstract: This article aims to find the existence of Emotional Intelligence as a servant's response in Habakkuk's paradigm shift towards God based on his book. This research shows that Habakkuk as a servant facing a crisis, experienced a paradigm shift towards God with excellent emotional management. The method used is thematic analysis modeling the doctrine of God. The results of the study found that EI, specifically stress management, decision making and Habakkuk's emotional expression were very good in responding to his condition. This finding is based on Habakkuk's paradigm shift, which begins in chapter 1 where his emotions are disturbed so that he questions God's justice and shows good stress management. Chapter 2 Habakkuk made the decision to keep waiting for God's answer and accept His decree. Chapter 3 Habakkuk shows emotional expression by offering prayers and adoration to God and closes his book with a firm statement of faith. This confirms that Habakkuk experienced a paradigm shift regarding God, from doubting and questioning God's justice to exalting God and triumphing in God.Â Keywords: Servant, Habakkuk, Emotional Intelligence, Paradigm